Improving Class X. 2 Students’ Speaking Achievement Under Round Robin Technique - Istiqomah Nur Rahmawati; . Syafriadin; Rizki Widiastuti (International Conference on Education and Language (ICEL), 2013)
This study investigated about the improving students’ speaking achievement. The scope of this study only focused on speaking accuracy. The hypothesis of the study was “If Round Robin is used effectively in teaching speaking at class X.2.  This investigation was conducted at class X.2 of senior high school in Bandung. The numbers of students were 29 students, 12 female and 17 male students. The design of this research was classroom action research which applied four steps. The steps were planning, action, observation and reflection. This research was conducted in two cycles which applied four types of instruments namely observation sheet, handy camera, speaking test, note taking. The expected target of the students’ accuracy was 70% mastery from each rater. In this research, qualitative and quantitative data had been collected and were analyzed by describing them into words and by using descriptive statistic. The finding showed that there was improvement of students speaking achievement. It could be proved from the mean score from cycle one to cycle two. The procedures of this technique consisted of six rounds and six speakers. each speaker was given a time to speak about the topic, after that the member asked a questions to the speaker. Then, speaker moved to the next group. In the first cycle, students faced some problems related to pronunciation, grammatical mistakes, and vocabulary and noisy. Due to this phenomena should be solved in each cycle. In the second cycle, students got improvement and students got less problems and students achieved the standard of achievement. Next, the cycle was stopped. In cycle one, the mean score was only 67.30. While, at the end of cycle two the mean score of students’ accuracy was 72.7. Therefore, we can say that there was an improvement about from cycle one to cycle two. This average achieved the target for accuracy decided by writer and teacher that was 70. This improvement in accuracy revealed that Round Robin technique positively and significantly improves X.2 students speaking achievement at senior high school in Bandung.